Validation of anthropological measures of the human femur for sex estimation in Brazilians - Cuzzullin, Maria Cláudia; Curate, Francisco; Freire, Alexandre Rodrigues; Costa, Sarah Teixeira; Prado, Felippe Bevilacqua; Daruge Junior, Eduardo; Cunha, Eugénia; Rossi, Ana Cláudia (Australian journal of forensic sciences, 2022)
The femur has been commonly employed for sex determination of human skeletal remains, and it is a suitable alternative to the more sexually dimorphic pelvis when this skeletal region is incomplete or fragmented. The purposes of this study include the evaluation of femoral sexual dimorphism and the generation of specific metric standards for the estimation of sex with the femur in skeletal Brazilian populations. Two hundred femora (130 males and 70 females) of known age at death, sex, and ancestry were used to generate the models for sex prediction. The best estimators of sex were univariable models, including the biomechanical neck length (BNLF, accuracy under cross-validation: 82.5%), the vertical head diameter (VHDL, accuracy under cross-validation: 81.5%), the transverse head diameter (THDF, accuracy under cross-validation: 84.5%), and the epicondylar breadth (EBF, accuracy under cross-validation: 84.5%). In conclusion, a comprehensive anatomical study of the femur in a reference skeletal sample from Brazil was provided, and the value of univariable sex estimators (BNLF, VHDL, THDF and EBF) was established.